The study of communication between distributed generation devices in a smart grid environment - Dias, Jefferson Aparecido [UNESP]; Serni, Paulo José Amaral [UNESP]; Godoy, Eduardo Paciência [UNESP] (My University, 2018)
The increasing use of electricity due to the population growth in recent years has resulted in a necessary expansion of the energy matrix through alternative sources, including microprosumers in low or medium voltage. Therefore, studies have been conducted to use the automation to control systems, but there is difficulty in establishing what will be controlled and how to get the data effectively. In the Microgrids scenario, one of the challenges is the network communication process between different devices, such as generators controllers, smart meters, etc., in order to facilitate the information exchange and improve network performance. Therefore, this chapter presents a study of a Microgrid (MG) with a Distributed Generator (DG) controlled remotely via a wireless communication. The methodology is presented by smart grid simulations, where the electrical system was implemented using the software PLECS - blockset, the wireless network was developed using TrueTime - toolbox, both emulated in Matlab®/Simulink®. In this application of MG, it was used a WLAN and ZigBee network to control the generation of the active power of and is evaluated under different network parameters, such as the loss probability and distance between devices. The simulation results show that the effectiveness of networked solution for developing MG. The results show that the simulation system provided a solution for the communication networks analysis, the DG control and modeling of electrical network in the smart MG, showing the effectiveness of the network solution for the development of MG.
Keywords: Distributed generation; Integrated simulation; Smart grids; Smart system; Wireless network